2010
DOI: 10.1021/jp910703n
|View full text |Cite
|
Sign up to set email alerts
|

Pentacene Multilayers on Ag(111) Surface

Abstract: The structural profiles and electronic properties of pentacene (C 22 H 14 ) multilayers on Ag(111) surface has been studied within the density functional theory (DFT) framework. We have performed first-principle total energy calculations based on the projector augmented wave (PAW) method to investigate the initial growth patterns of pentacene (Pn) on Ag(111) surface.In its bulk phase, pentacene crystallizes with a triclinic symmetry while a thin film phase having an orthorhombic unit cell is energetically less… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 55 publications
4
38
0
Order By: Relevance
“…6, in agreement with experimental observations 10,45,46 . Our results are also in good agreement with previous theoretical studies: from PBE calculations we found d = 3.938Å and E ads = −0.119 eV, which compare well with previous GGA results (d = 3.7-4.12Å and E ads within the range of −0.078 to −0.108 eV) 47,48 ; using the PBE+vdW surf method we found d = 2.910Å and E ads = −2.396 eV, which is in good agreement with previous results obtained by Toyoda et al 47 using the pairwise DFT-D method (d = 2.9Å and E ads = −2.28 eV), but differ from the values obtained by the same authors using the nonlocal vdW-DF method (d = 3.7Å and E ads = −1.62 eV) 47 . It should be pointed out that the vdW-DF method tends to overestimate the adsorption heights, even though it provides reliable adsorption energies 12,22 -recent vdW-DF functionals (e.g., optB86b-vdW and rev-vdW-DF2), however, have been shown to give both accurate adsorption height and energy 49 .…”
Section: B Pentacene On Ag(111)supporting
confidence: 93%
“…6, in agreement with experimental observations 10,45,46 . Our results are also in good agreement with previous theoretical studies: from PBE calculations we found d = 3.938Å and E ads = −0.119 eV, which compare well with previous GGA results (d = 3.7-4.12Å and E ads within the range of −0.078 to −0.108 eV) 47,48 ; using the PBE+vdW surf method we found d = 2.910Å and E ads = −2.396 eV, which is in good agreement with previous results obtained by Toyoda et al 47 using the pairwise DFT-D method (d = 2.9Å and E ads = −2.28 eV), but differ from the values obtained by the same authors using the nonlocal vdW-DF method (d = 3.7Å and E ads = −1.62 eV) 47 . It should be pointed out that the vdW-DF method tends to overestimate the adsorption heights, even though it provides reliable adsorption energies 12,22 -recent vdW-DF functionals (e.g., optB86b-vdW and rev-vdW-DF2), however, have been shown to give both accurate adsorption height and energy 49 .…”
Section: B Pentacene On Ag(111)supporting
confidence: 93%
“…For example, when moving from a pure to a mixed donor/acceptor molecular monolayer on the same metal substrate. These systems have stimulated much interest for both experimentalists and theorists, particularly for olefins, 16 pentacene, [17][18][19][20][21][22][23][24] perfluorinated pentacene, [25][26][27] their 1:1 mixture, [28][29][30][31] copper phthalocyanine, [32][33][34][35][36][37] and fluorinated phthalocyanine, [38][39][40] on the (111) facet of the coinage metals. It has been repeatedly reported that such two-dimensional blending of donors and acceptors gives rise to core-level shifts in all atomic components.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structures of iodine-and rubidium-doped pentacene molecular crystals have also been investigated by ab-initio calculations based on the ultrasoft pseudopotential method, predicting a metallic behavior [19]. Recently, the structural and electronic properties of pentacene multilayers on the Ag(111) surface have been studied, revealing that pentacene has no electronic contribution at the Fermi level [20]. To describe the dielectric behavior, a general oscillator approach consisting of Gaussian peaks in the imaginary part of the dielectric function ε 2 (E) was applied (more detailed information about the fitting procedure and the Gaussian parameters can be found in the supporting information).…”
Section: Introductionmentioning
confidence: 99%